2007
DOI: 10.1007/s00540-006-0441-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of a wire-guided cannula for radial arterial cannulation

Abstract: We compared the success rates of arterial cannulation with a wire-guided cannula (WGC) and the direct technique with a conventional non-wire-guided cannula (non-WGC). A total of 100 adult patients requiring an arterial line in the operating room were assigned randomly to undergo radial arterial cannulation either with the WGC or with the non-WGC. No significant difference in success rates and insertion times could be demonstrated between the WGC and the non-WGC (78.4% vs 67.3% and 22.6 +/- 13.2 s vs 23.0 +/- 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The through-and-through technique was used only as a backup approach because it often produces a hematoma beyond the vein’s posterior wall, which can compromise subsequent catheterisation attempts should one prove necessary. The benefits [ 32 - 34 ] and difficulties [ 35 ] of other techniques to facilitate vessel catheterisation, including using guide-wires and the bevel-down approach, are well verified in adults but remain poorly evaluated in paediatric patients [ 33 ]. Ultrasound-guided peripheral venous catheterisation may be more successful when combined with these ancillary techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The through-and-through technique was used only as a backup approach because it often produces a hematoma beyond the vein’s posterior wall, which can compromise subsequent catheterisation attempts should one prove necessary. The benefits [ 32 - 34 ] and difficulties [ 35 ] of other techniques to facilitate vessel catheterisation, including using guide-wires and the bevel-down approach, are well verified in adults but remain poorly evaluated in paediatric patients [ 33 ]. Ultrasound-guided peripheral venous catheterisation may be more successful when combined with these ancillary techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques for improving radial artery cannulation have included performing the modified Allen test and/or Barbeau test to assess for patency of the vessel [5], direct visualization of the vessel with ultrasonography at the time of cannulation, and use of a wireguided cannula [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…3,12 This result is likely due to the smaller size of the female radial artery. Our study focused on the relationship between the diameter of the radial artery and the angle of the wrist joint, and showed that excessive extension of the wrist joint angle reduces arterial size.…”
Section: Discussionmentioning
confidence: 99%